IDENTIFIKASI SESAR AKTIF DAERAH CEKUNGAN BANDUNG DENGAN DATA CITRA LANDSAT DAN KEGEMPAAN - Marjiyono Marjiyono; Asdani Soehaimi; Kamawan Kamawan (Jurnal Geologi dan Sumberdaya Mineral, 2008)
Seismic monitoring around Bandung basin since 1999 - 2006 which has been carried out by the Seismological Laboratory, Geological Survey Institute, had recorded nine earthquakes. Epicentre location of the earthquakes indicated that the earthquakes are associated with the lineaments interpreted on landsat image. It is concluded that there are at least five active faults in this area such as Tanjungsari - Cileunyi, Lembang, Cicalengka, Jati and Legok Kole fault. Keywords: active fault, epicenter, lineament, landsat image